Timing of percutaneous coronary intervention in troponin-negative patients withacute coronary syndrome without persistent ST-segment elevation: preliminary results and status quo in German chest pain units - Breuckmann, Frank; Hochadel, Matthias; Münzel, Thomas; Giannitsis, Evangelos; Voigtländer, Thomas; Senges, Jochen (Critical pathways in cardiology, 2015)
Objective:Management of acute coronary syndromes without persistent ST-segment elevation (NSTE-ACS) and unstable angina pectoris (UAP) remains challenging. The study aimed to analyze the current management of UAP patients in German chest pain units focussing on the different time lines of invasive s
Gesehen am 28.05.2020